Corruption Perceptions and Stock Market Performance: Evidence from Bursa Malaysia - Hadi, Abdul Razak Abdul; Hashim, Mohd Hisham; Ibrahim, Alisa (International Journal of Psychosocial Rehabilitation, 2020)
Studying the relationship between corruption and economic factors, particularly the perception of corruption upon capital market developments has attracted worldwide attention among economists and researchers in recent years. The purpose of this paper is to investigate how ranking in corruption index may exert some significant influence on Malaysian stock market, that is, Bursa Malaysia. Extracting time series data from Transparency International’s corruption index and Malaysian stock market barometer from 1995 through 2018, we discover some degree of dependency between this Corruption Perception Index (CPI) and Kuala Lumpur Composite Index (KLCI). This study employs Ordinary Least Square (OLS) Regression as an estimation method and the empirical findings are somewhat consistent with the previous literature on similar subject matter